Development and Quality Evaluation of High Value Pet Food (Pet Treat) - Gogoi, Protiva; Hazarika, Mineswar; Deuri, Deepshikha; Das, Ankur; Upadhaya, Santosh (Journal of Meat Science, 2019)
Local availability of dog feeds is less and quite a big volume of dog feeds are being imported to city regularly from outside. Because of the higher cost of commercial dog feeds, most of the dog owners cannot afford to provide these feed to their pets. With this intention in mind, a few pet treats were developed taking pork by products as basic protein ingredient and incorporating vegetable by products as secondary ingredient. Four different pet treats were prepared combining meat and non-meat by products using four different binder combinations viz. Treatment- 1(Maida), Treatment-2 (Rice bran), Treatment- 3 (Wheat bran) and Treatment- 4 (Maida, Rice bran, Wheat bran and molasses). The products were dried in hot air oven at about 80oC for 24 hours. The products were vacuum packed in high den sity polyethylene packaging material and kept at room temperature for quality assessment. No significant differences in moisture, crude protein, ether extract, carbohydrate and calorie content of the prepared pet treats were observed. However, significant difference could be observed in pet treats prepared with addition of maida (Treatment 1) and wheat bran (Treatment 3) with respect to the ash content of the samples. The pet treats were found to be highly acceptable by different breeds of dogs. The costs of production of per kg pet treats were found to be Rs. 245.00, Rs. 240.00, Rs. 240.00 and Rs. 250.00 for treatment 1, treatment 2, treatment 3 and treatment 4 respectively. The products can be commercially developed and may be marketed locally for dog owners of Guwahati city.